If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -6) + -8x = 2x Reorder the terms: 5(-6 + x) + -8x = 2x (-6 * 5 + x * 5) + -8x = 2x (-30 + 5x) + -8x = 2x Combine like terms: 5x + -8x = -3x -30 + -3x = 2x Solving -30 + -3x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -30 + -3x + -2x = 2x + -2x Combine like terms: -3x + -2x = -5x -30 + -5x = 2x + -2x Combine like terms: 2x + -2x = 0 -30 + -5x = 0 Add '30' to each side of the equation. -30 + 30 + -5x = 0 + 30 Combine like terms: -30 + 30 = 0 0 + -5x = 0 + 30 -5x = 0 + 30 Combine like terms: 0 + 30 = 30 -5x = 30 Divide each side by '-5'. x = -6 Simplifying x = -6
| (x-4)(x+5)(x+10)(x-2)=18x^2 | | 5g+3=17 | | 3(2x+6)+2(7x-4)+10x=8x+2(x+9) | | [11-4x]-7=95-15x | | f=-19x | | t^4-3t^3-28t^2=0 | | -7.2+(-2.7)= | | 25=q-20 | | f=1+-20x-1+x | | 6x-4+2x+8=180 | | 10x-2+44=180 | | x^3-3x^2-6x-6=0 | | 3x+5+4x+1=90 | | 6a-12=2a+4 | | 2x/3-3(x-2)/5 | | 10x-6+8x+24=180 | | X-3+2x+6=90 | | (2x^-5y^2)^-2/8z= | | x^2+7c=8 | | c=14d | | (25x^(5/3))(X^(2/3)) | | g(-2)=6x^2-9x-10 | | 2.4/0.4 | | 68x+4x^2=672 | | (x+6)2+(y-5)2=8 | | 2x^2=24+13x | | -2/7•5/8 | | -2/7x5/8 | | -2q^2+7q+11=1 | | 3sin(x)-5x=4 | | 3x-(2-x)=6 | | x+5cos(x)=6 |